a We are given the following radical equation
![2\sqrt[]{n}=n-3](https://img.qammunity.org/2023/formulas/mathematics/college/lkxretc2brq72c83n8q0mx2s9pj6dx1p30.png)
To solve this equation we need to square both sides of the equation
![\begin{gathered} (2\sqrt[]{n})^2=(n-3)^2 \\ 4n=(n-3)^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3p9g9d7jz5wbvoviumxlcornosp5jrz2jz.png)
Apply the squares formula on right-hand side of the equation
![(a-b)^2=a^2+b^2-2ab](https://img.qammunity.org/2023/formulas/mathematics/high-school/l1jzbrn4g64u4ww1qz0oyxkvxo0pyxdw32.png)
So the equation will become
![\begin{gathered} 4n=n^2+3^2-2(n)(3) \\ 4n=n^2+9-6n \\ 0=n^2+9-6n-4n \\ 0=n^2+9-10n \\ n^2-10n+9=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p8mtsb4mkn8g3e5qphsmt5exrn5j1dnmo8.png)
So we are left with a quadratic equation.
The standard form of a quadratic equation is given by
![ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/mvkhuzwnjhb4epaf7jjcoq2vi4zdi4350m.png)
Comparing the standard equation with our equation we get the following coefficients
a = 1
b = -10
c = 9
Now recall that quadratic formula is given by